2021
DOI: 10.21307/aoj-2021-002
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of incipient carious lesions with various interventions during fixed and removable orthodontic treatment. A systematic review and meta-analysis

Abstract: To systematically review and quantify the effectiveness of interventions in reducing caries development during orthodontic treatment and evaluate the quality of evidence for the development of clinical guidelines. Materials and methods: A comprehensive literature search of the Cochrane, EMBASE and MEDLINE databases was conducted to identify eligible randomised controlled trials (RCTs). The risk of bias was assessed using the Cochrane risk of bias (RoB 2) tool. In order to facilitate the development of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The exposure to fluoride via regular mouth rinses and or fluoridated toothpastes has been shown to be an effective preventive measure during orthodontic treatment. 12 In addition, the application of casein phosphopeptide-amorphous calcium phosphate (CCP-ACP) in combination with Sodium Fluoride gel, can help to reduce enamel demineralisation and promote remineralisation of early lesions. 13 Regrettably, patient compliance in following instructions in these preventive measures is a limiting factor in successful caries prevention.…”
Section: Fixed Appliance Orthodontic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure to fluoride via regular mouth rinses and or fluoridated toothpastes has been shown to be an effective preventive measure during orthodontic treatment. 12 In addition, the application of casein phosphopeptide-amorphous calcium phosphate (CCP-ACP) in combination with Sodium Fluoride gel, can help to reduce enamel demineralisation and promote remineralisation of early lesions. 13 Regrettably, patient compliance in following instructions in these preventive measures is a limiting factor in successful caries prevention.…”
Section: Fixed Appliance Orthodontic Treatmentmentioning
confidence: 99%
“…However, new carious lesions can develop in as little as four weeks 11 and as the interval between orthodontic appointments can be up to eight weeks, may remain undetected by the practitioner. The exposure to fluoride via regular mouth rinses and or fluoridated toothpastes has been shown to be an effective preventive measure during orthodontic treatment 12 . In addition, the application of casein phosphopeptide‐amorphous calcium phosphate (CCP‐ACP) in combination with Sodium Fluoride gel, can help to reduce enamel demineralisation and promote remineralisation of early lesions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nevertheless, removable orthodontic treatment has an increased risk of dental caries as an adverse effect. 7 According to Mathews et al the incidence of white spot lesion development is 1.2% during removable orthodontic treatment. Although this incidence is far lower than those with fixed orthodontic appliances (26%), removable appliances are capable of changing the microbial flora of the oral cavity, which may result in dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Although this incidence is far lower than those with fixed orthodontic appliances (26%), removable appliances are capable of changing the microbial flora of the oral cavity, which may result in dental caries. 7,8 Lucchese et al reported that past studies have proven that there is an increase in S. mutans and Lactobacillus spp in patients using removable orthodontic appliances. 9 This may be caused by removable appliances covering all or part of tooth surfaces which affects the flushing effect of saliva, creates niches for cariogenic microorganisms to develop and persist, and leads to an ecological shift.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation